Tereny nadrzeczne jako miejsce spędzania czasu wolnego mieszkańców Bydgoszczy = Riverside areas as places of leisure inhabitants of Bydgoszcz - Iwona Józefowicz (Kazimierz Wielki University, 2015)
Józefowicz Iwona. Tereny nadrzeczne jako miejsce spędzania czasu wolnego mieszkańców Bydgoszczy = Riverside areas as places of leisure inhabitants of Bydgoszcz. Journal of Education, Health and Sport. 2015;5(12):555-562. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44218 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A555-562 http://pbn.nauka.gov.pl/works/686569 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015.   TERENY NADRZECZNE JAKO MIEJSCE SPĘDZANIA CZASU WOLNEGO MIESZKAŃCÓW BYDGOSZCZY RIVERSIDE AREAS AS PLACES OF LEISURE INHABITANTS OF BYDGOSZCZ   Iwona Józefowicz   Instytut Geografii, Wydział Kultury Fizycznej Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy           Słowa kluczowe: Bydgoszcz, Bydgoski Węzeł Wodny, tereny nadrzeczne, czas wolny,   Abstrakt   Celem artykułu jest omówienie wyników badań związanych z postrzeganiem terenów nadrzecznych jako miejsc spędzania czasu wolnego w Bydgoszczy. Większość ankietowanych mieszkańców Bydgoszczy spędza swój czas wolny na terenach Bydgoskiego Węzła Wodnego. Wśród preferowanych form znajdują się spacery, wycieczki piesze i rowerowe oraz uczestnictwo w imprezach plenerowych. Ocena terenów nadrzecznych jest zróżnicowana, obok odcinków postrzeganych pozytywnie są także te z notami negatywnymi.       Key words: Bydgoszcz, Bydgoski Węzeł Wodny, riverside areas, leisure.   Abstract   The article presents the results of studies related to the perception of riverside areas as places of leisure in Bydgoszcz. The majority of surveyed inhabitants of Bydgoszcz spends his free time in the areas of Bydgoski Węzeł Wodny Among the preferred forms are walking, hiking and biking trips and participation in outdoor events. Rating riverside areas is different. some areas are seen positively as those with negative notes.